Pemanfaatan Platform Digital pada UMKM dalam Meningkatkan Daya Saing Usaha : Pendekatan Netnografi - Liya Setiawati; Edwin Karim; Wiwit Pawitri (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2024)
Digital transformation has become a crucial factor in enhancing the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) amidst the changing global economic landscape. This study aims to explore how MSMEs utilize digital platforms, the strategies used to optimize their online presence, and the challenges faced during the digitalization process. The research method uses a netnographic approach, namely an ethnographic study conducted in the digital realm, by combining participatory and non-participatory observations of MSME community activities on various digital platforms, such as Facebook, Instagram, and online marketplaces (Shopee, Tokopedia, and the like) during the period of January to March 2025. Researchers observed communication patterns, content strategies, and interactions between MSME actors and consumers. Data were analyzed using a thematic analysis approach to identify key themes that reflect digital marketing strategies, forms of innovation, and barriers to digital technology adoption. The results show that digital platforms are not only used as promotional media, but also as a means to build consumer trust, expand distribution and marketing networks, and encourage product and service innovation. MSMEs actively utilize features such as live streaming, customer reviews, and collaborations with local influencers to increase product visibility. However, MSMEs still face various obstacles, such as limited digital literacy, a lack of understanding of platform algorithms, limited capital for paid digital promotions, and increasingly fierce competition in the digital ecosystem. Technical barriers, such as uneven internet access and a lack of technological assistance, also slow down the digitalization process. This research contributes to the literature on MSME digitalization in Indonesia using a contextual netnography approach. Furthermore, the study's findings offer practical recommendations for businesses to optimize the use of digital platforms and for policymakers to design more targeted assistance programs, particularly to increase the digital capacity of MSMEs in the regions.